2015
DOI: 10.1186/s40249-015-0078-5
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection with malaria and intestinal parasites, and its association with anaemia in children in Cameroon

Abstract: BackgroundThe purpose of this study was to determine the prevalence of coinfection with malaria and intestinal parasites, as well as to determine its association with anaemia in children aged 10 years and below in Muyuka, Cameroon.Materials and methodsThis was a cross-sectional study. Participants were febrile children who were admitted to the Muyuka district hospital between April and October 2012. Blood and stool samples were collected from those participants who gave consent to take part in the study. Haemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
39
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 38 publications
14
39
8
1
Order By: Relevance
“…Conversely, prevalence of malaria in the current study was not observed to be associated with gender or study site. The finding of no association between prevalence of malaria and gender is in conformity with other studies [3] [4] [5] [7].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Conversely, prevalence of malaria in the current study was not observed to be associated with gender or study site. The finding of no association between prevalence of malaria and gender is in conformity with other studies [3] [4] [5] [7].…”
Section: Discussionsupporting
confidence: 92%
“…Although there has been a decline in malaria recently, malaria still remains a significant cause of morbidity and mortality in SSA, claiming the live of a child every 2 minutes [2]. In Cameroon, malaria is a major cause of morbidity and mortality among children [3] [4] [5]. Malaria is caused by parasitic protozoans of the genus Plasmodium.…”
Section: Introductionmentioning
confidence: 99%
“…Malaria in Yaounde can be described as holoendemic and seasonal [18]. The prevalence is also very low compared to the prevalence of malaria in the other high risk groups including children (where prevalence could be as high as 98 % in some settings) [24], and pregnant women [25]. The low prevalence of malaria in this group could be attributed to the health seeking attitude of HIV patients.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the prevalence of anaemia in these studies compared to ours could be attributed to the differences in the nutritional habits of these populations. Malnutrition and infectious diseases (such as malaria, intestinal parasitic infections, HIV) are some of the main factors contributing to the high prevalence of anaemia especially in children in Cameroon [12]. The high prevalence of anaemia implies 31.44% of the donors were deferred as a result of the anaemia over the year thereby constituting a huge loss of blood stock.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition is one of the main culprit for anaemia in Africa [9]. In addition to malnutrition, there are also infectious causes of anaemia in Cameroon including malaria and intestinal parasitic infections [10–12]. …”
Section: Introductionmentioning
confidence: 99%